Improving the Learning Outcomes of PAI Class IV by Using the Indexcard Match Method at SDN 04 Langung Saiyo - Masripa Hanum (BiCED Proceeding, 2024)
The learning outcomes of Islamic Religious Education (PAI) at SD N 04 Langung Saiyo remain low, as evidenced by scores that have not reached the Minimum Completion Criteria (KKM) of 75. This is due to the use of monotonous teaching methods, low student participation, and poor problem-solving skills. This study aims to examine the improvement of student activity in Grade IV of SD N 04 Langung Saiyo and their learning outcomes after the implementation of the Problem-Based Learning (PBL) model on the material of Q.S Al-Hujurat verse 13 and Hadith about diversity. This research uses Classroom Action Research (CAR) with the stages of planning, implementation, observation, and reflection carried out in three cycles. Cycle I was conducted on December 21, 2024, with 17 students, consisting of 8 males and 9 females. The results indicate that the implementation of the PBL model can improve both learning outcomes and student activity in the learning process. In cycle I, there was an improvement in the average score and the classical completeness percentage, with an average completeness percentage of 66.33%. This study concludes that the PBL model can be an effective alternative for improving learning outcomes and student participation in PAI education at SD N 04 Langung Saiyo.